A cross-sectional study of acute dengue infection in paediatric clinics in Cameroon - Tchuandom, Salomon Bonsi; Tchadji, Jules Colince; Tchouangueu, Thibau Flaurant; Biloa, Monique Zambo; Atabonkeng, Etienne Philémon; Fumba, Marcelle Irina Miste; Massom, Eithel Sylvian; Nchinda, Godwin; Kuiate, Jules-Roger (BMC public health, 2019)
Dengue fever is the world's fastest spreading mosquito borne viral infection. It is prevalent throughout both subtropical and tropical region, and affects over 128 countries. Dengue virus (DENV) infection poses a serious global public health challenge to three billion people, resulting in approximately 200 million cases of morbidity and 50,000 cases of mortality annually. In Cameroon like in most sub-Saharan African countries, DENV infection occur concurrently with other infectious diseases whose symptoms often overlap, rendering differential diagnosis challenging. This study aims at determining the frequency of acute dengue among febrile children under 15 years attending hospitals in some areas of Cameroon. A total of 961 children under the age of 15 were recruited in a cross-sectional study using systematic sampling technique and by selecting each subject out of the three. The study was conducted in 10 public health centers in Cameroon. Demographic data and risk factors of the subjects were obtained using well-structured questionnaires. Dengue virus NS1 antigen, IgM and IgG were analysed using a Tell me fast® Combo Dengue NS1-IgG/IgM Rapid Test. An in-house ELISA test for dengue specific IgM antibody was equally performed for confirmation. Descriptive statistical analysis was performed using Graph pad version 6.0. A prevalence of 6.14% acute dengue virus infection was observed among children with febrile illness with a significant difference (p = 0.0488) between males (4.7%) and females (7.7%). In addition, children who reportedly were unprotected from vectors, showed a comparatively higher prevalence of the disease seropositivity than those practicing protective measures. DENV infection therefore is an important cause of fever among children in Cameroon. Thus, there is a need to include differential screening for DENV infections as a tool in the management of fever in children in the country.